10.3928/02793695-20090201-02 (CrossRef Listing of Deleted DOIs, 2000)
Background Students in their clinical practice are exposed to high stress and an academically intense workload. Clinical instructors can play a supportive role in helping nursing students cope with stress and achieve clinical outcomes. The aim of this scoping review was to identify how clinical instructors affect resilience in undergraduate nursing students during clinical education. Method A scoping review was conducted. Three databases were searched. Eligibility criteria included primary research involving nursing students within their clinical education that addressed the instructor's role in developing resilience, coping, and adaptation. A total of 3,039 citations were screened; four articles met inclusion criteria. Results Themes included: (1) instructors have ability to equip students to use coping strategies; (2) instructors teaching characteristics; (3) supporting student capacity development, which enables more resilience; and (4) instructor influence on clinical learning environment. Conclusion Intentional and effective instruction can enhance students' resilience, strengthen their coping capacity, and contribute to their competency development.